Epidemics in Modern and Contemporary Age in a Backward Area of Europe: The Role of Institutions and Socio-Economic Effects in Southern Italy (European Journal of Marketing and Economics, 2020)
Ethics as a cure for anxiety, or rather for anxieties, a distinctive feature of contemporary western man, neurotic and afraid. Man cannot be only that aggregate of primitive instincts driven by selfishness and individual interest that utilitarianism has credited and neoliberalism has emphasized. It seems obvious that the Covid-19 effect amplifies these paradoxes and anxieties. Epidemics are certainly not new in the historical-social context. The purpose of this study will be to analyze some of the numerous epidemics that have occurred in history and their impact on the economy. The corrections can only come from a re-evaluation of the ethical state, the ethical family and a new ethical world: attention to migratory phenomena through the principle of the obligation to rescue the least of the earth; relaunch of the international organizations with which the world, in the happy post-war season, had intended to give an order that guaranteed peace and balance, but which has gradually been forgotten; reduction of wage differences; taxation of capital and presence of the public interest in the company's governing bodies. Through the analysis of original sources, such as the historical archive of Pio Monte della Misericordia and Banco di Napoli, the study will compare the plague of 1656, and the effects of the intervention of charities in support of the population with the socio-economic impact of the Spanish influence in the first decades of the twentieth century, up to the current pandemic, with particular attention to the consequences on the production capacity of goods and services in a backward area of Europe, such as Southern Italy. *
Keywords: Economic History; Social Sciences; Economic impact; Epidemics.